Pengaruh Lingkungan Kerja terhadap Produktivitas Kerja Karyawan PT. Biringkassi Raya - Moh. Filzan Al-Mustajidi; Agung Widhi Kurniawan; Zainal Ruma (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The method used in this research is a quantitative method and primary data sources. Meanwhile, to analyze the data obtained, instrument tests, classical assumption tests and hypothesis tests were used with the help of SPSS 24. Based on the results of the analysis, it can be concluded that the Work Environment variable has a partial effect on Employee Work Productivity. The statistical calculation results of the T test show that Tcount is 15.211, meanwhile the Ttable value = 2.04, so Tcount > Ttable and the significance value is 0.000 < 0.05. The results of this analysis accept the first hypothesis. This finding also strengthens the respondents' answers which show that every statement related to the work environment was responded to with good answers. PT Biringkassi Raya in carrying out its main tasks and functions always strives to improve its capabilities to achieve its planned goals. The work environment is the entire work facilities and infrastructure around employees who are doing work which can affect the work itself. Basically, the work environment is everything that is around workers and can influence them in carrying out their duties.